Um estudo de relações da constituição das significações na filosofia de Peirce e na psicanálise - Guimarães Filho, Paulo Duarte (2019)
The main purpose of this study is to examine relationships and parallels between the ideas about the constitution of meaning in Peirce’s philosophy and in psychoanalysis, as formulated by two of its well-known authors, Wilfred Bion and Donald Winnicott. The basis for this investigation is the recognition of how Peirce’s categories, and the theory of signs that is part of his philosophy, were related to ideas independently developed in psychoanalysis, such as Bion’s alpha function and Winnicott’s transitional objects and phenomena. In this context, our research was guided by Peirce’s proposal, in “A Guess at the Riddle”, that the application of his categories to psychology, by means of a kind of play that he called, “follow my leader”. By following his thread, we came to the relevant realization that Peirce’s proposal had been to a certain extent accomplished, in an independent way and in other words, through some of Bion’s ideas described in details in this study. Peircean’s ideas led to clarifications and improvements in conceptual and clinical psychoanalytic notions, particularly those of alpha function, the “Grid” and Bion’s theory of transformations. We also describe how Peircean ideas could be useful to an international discussion about the called “late Bion”; another significant Peircean contributions were to expanding concepts such as that of transitional objects and playing by Winnicott. Finally, we described how the study of the close relationships between the ideas of Peirce, with Bion and with Winnicott, also allowed us to identify similarities between Bion’s alpha function and the role of playing in Winnicott